Reducing the emergence and spread of waterborne antimicrobial resistance (AMR) in Ethiopia from a One Health perspective - Graham, D. W.; Mateo-Sagasta, Javier; Haile, Alemseged Tamiru; Moodley, A.; Goshu, G.; Kibret, M. (International Water Management Institute (IWMI). CGIAR Initiative on One Health, 2024)
Antimicrobial resistance (AMR) is an increasing global health problem with serious impacts in Ethiopia. Environmental waters play a key role in the transmission and spread, and potentially in the development of resistance. The elevated presence of AMR and antimicrobials in Ethiopian water systems arises from inadequate waste management coupled with poorly regulated antimicrobial use (AMU) in the human, animal and agricultural sectors. The continued and inconsistent use of antimicrobials by healthcare providers and community-scale drug consumption drives AMR development in the gut of users, which spreads via wastes and water in Ethiopia. However, the massive use and misuse of antimicrobials is also common among animal health care providers, including unskilled and animal husbandry practitioners, which also results in waste releases and the environmental transmission and spread of AMR.